Successful Removal of Metal Objects Causing Penile Strangulation by a Silk Winding Method - Chuanjiang Dong; Ziqiang Dong; Fei Xiong; Zonglan Xie; Qiaoli Wen (Case Reports in Urology)
Penile strangulation is a challenge to urologists. The decompression of the penis is required to prevent long-term complications. Metal objects are difficult to remove. Cutting is the most common method described. Appropriate cutting tools may be difficult to obtain, and the process may be time-consuming with the possibility of iatrogenic penile injury. In this paper, we will present a simple method to remove such objects by use a silk winding method and subcutaneous puncture.